Use of a national database for strategic management of municipal oral health services for Danish children and adolescents - Hansen I, Foldspang A, Poulsen S (Blackwell Synergy, 2001)
To evaluate the use of a national register for strategic management of dental health services for 0–17-year-old Danish children and to identify determinants for their use of the system as a strategic tool in management of the services.